ҒАЛАБАЛЫҚ МӘДЕНИЯТТЫҢ МӘНИСИ ҲӘМ МӘНАЎИЯТЫМЫЗҒА ТӘСИРИ - Базарбаев, Ж.; Жақсымуратова, Н. (FAN va JAMIYAT, 2019)
The article gives information about mas-culture and its today’s, impact, its spiritual image and negative effects.